Investigating the usage of self ordering kiosk towards customer behavior: a case on McDonalds/ Siti Asma Yaacob ... [et al.] - Yaacob, Siti Asma; Abdul Aziz, Azdel; Ahmad, Noor Azmi; Ismail, Mohd Noor Ismawi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The introduction of Self-Service Technology (SST) has influenced the acceptance of consumers toward the use of SST in the service sector, especially the restaurant industry. This study intended to analyze the factor that influencing consumer acceptance on using self-ordering kiosks in McDonald’s by using The Unified Theory of Acceptance and Use of Technology (UTAUT). Besides, this study focused on to examine the independent variable of UTAUT (Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating condition) and their relationship toward behavioral intention and use behavior. The data was gathered from 400 respondents that have been used the kiosk through questionnaire by using a convenience sampling method. The finding of the result reveal that Performance Expectancy, Social Influence and Facilitating Condition has significant influence toward consumer behavioral intention to use Self-Ordering Kiosks. However, contrary to other constructs, Effort Expectancy did not influence behavioral intention. In addition, finding revealed that consumer behavioral intention has significant influence toward the use behavior, indicating that the probability of the consumer to use the kiosk is high. On the other hand, this study has proven that behavioral intention has influence the use behavior as mediator for UTAUT. Overall finding revealed that facilitating conditions shows the highest influence on consumer behavioral intention on using self-ordering kiosks McDonald’s.